2015
DOI: 10.1002/anie.201411745
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II) Metallopeptide Catalyst Design Enables Fine Control in Selective Functionalization of Natural SH3 Domains

Abstract: Chemically modified proteins are increasingly important for use in fundamental biophysical studies, chemical biology, therapeutic protein development, and biomaterials. However, chemical methods typically produce heterogeneous labeling and cannot approach the exquisite selectivity of enzymatic reactions. While bioengineered methods are sometimes an option, selective reactions of natural proteins remain an unsolved problem. Here we show that rhodium(II) metallopeptides combine molecular recognition with promisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
0
46
0
4
Order By: Relevance
“…A complement to azido groups, diazo groups have been employed in many biochemical applications, including reversible 1 and non-reversible protein alkylations, 2 nucleic acid conjugation, 3 and other bioconjugations. 4 Extant strategies to install pendant diazo groups 5 and to prepare them directly by deimidogenation of a parent azide 6 facilitate their use.…”
Section: Introductionmentioning
confidence: 99%
“…A complement to azido groups, diazo groups have been employed in many biochemical applications, including reversible 1 and non-reversible protein alkylations, 2 nucleic acid conjugation, 3 and other bioconjugations. 4 Extant strategies to install pendant diazo groups 5 and to prepare them directly by deimidogenation of a parent azide 6 facilitate their use.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan was the most reactive side chain. Turnover numbers of up to 50 were obtained at micromolar substrate concentration, and the rate enhancement for complementary substrates relative to an unstructured control reaction was >10 3 . Even more powerfully, the proximity-driven catalysis enabled modification of many other side chains (Figure 1) that are completely unreactive with simple [1,2].…”
Section: Resultsmentioning
confidence: 97%
“…We examined modification of SH3 domains in significant detail [3]. The SH3 domain recognized short proline-rich motifs in an extended, PPII-helix conformation.…”
Section: Fig 1 Site-specific Covalent Modification Of Helical Peptimentioning
confidence: 99%
See 1 more Smart Citation
“…3 Even in water metal carbenes can still perform an impressive array of transformations. 47 In our studies on the post-synthetic tailoring of large nucleic acids through metal catalysis we have found that donor–acceptor substituted carbenes 8 derived from Rh( ii ) and Cu( i ) give primarily N–H insertion of exocyclic amine groups in unpaired regions of DNAs and RNAs. 911 Here we show that unstabilized Cu( i ) carbenes derived from α-diazo acetate and amide derivatives have a completely different chemoselectivity: they quickly and cleanly alkylate the O 6 position in guanine and inosine (see Fig.…”
Section: Introductionmentioning
confidence: 98%